The Synthesis of a 19 Kilodalton Zein Protein in Transgenic Petunia Plants - Williamson, John D. (1988)
Transcriptional fusions composed of a 19 kilodalton zein cDNA, the 5′ flanking region from a β-phaseolin gene, and 3′ flanking regions from either the phaseolin or a 15-kilodalton zein gene were introduced into Petunia by Agrobacterium-mediated transformation. The expression of both zein mRNA and protein in these transgenic plants was seed-specific and developmentally regulated. Both monocot (zein) and dicot (phaseolin) polyadenylation consensus sequences were recognized in Petunia. Analysis by immunoblotting showed that the M(r) of the zein protein corresponded to that of the mature protein, suggesting that recognition and cleavage of the signal sequence had occurred. While zein mRNA accumulated to approximately 1% of the total poly(A)(+) RNA in seeds of the transformed plants, zein protein was present at a much lower concentration than expected, at most being 0.005% of the total seed protein. These results suggest that the 19 kilodalton zein gene, in addition to lacking specific sequences required for efficient transcription in dicots, might also lack sequences required for the efficient synthesis, targeting, transport, or stabilization of the protein.